ChemInform Abstract: Bifunctional Building Blocks in the Ugi‐Azide Condensation Reaction: A General Strategy Toward Exploration of New Molecular Diversity. Issue 2 (14th January 2014) - Gunawan, Steven; Hulme, Christopher
Abstract Ugi‐azide reaction of tethered aldo/keto—acids/esters followed by a ring closing step opens access to a variety of complex lactam—tetrazoles.